Impact of Shopping Malls on the Unorganized Retail Sector: A Case Study of Mangalore Region - Ahmed, Ajaz; Mayya, Sureshramana (Indian Journal of Marketing, 2012)
Retailing is the largest private industry in India and the second-largest employer after agriculture. Organized corporate retailing is poised to become the business of this decade in India. The unprecedented growth of corporate retailing and the entry of major foreign retail players in the Indian retail market has caused concern that the small and marginal unorganized retailers will be adversely affected. The review of literature revealed that there are several global and Indian studies, which clearly indicates that there is a significant impact of organized retailing on the unorganised sector. In the backdrop of this appalling situation, the present study was undertaken to examine and investigate the extent of impact, and more specifically; an empirical attempt was made to answer certain critical and analytical questions with respect to the extent of impact of shopping malls on the unorganized retail sector in Mangalore, Karnataka.